Asia-Pacific Economic Cooperation : New Agenda in Its Third Decade - Yamazawa, Ippei, 1937- (Singapore : Institute of Southeast Asian Studies, 2012)
Ippei Yamazawa is one of the fathers to the study of Asia-Pacific regional cooperation in Japan and has contributed hugely to the development and work of APEC over many years. APEC is a crucial trans-regional arrangement that draws the United States into constructive economic engagement with East Asia. This book makes it clear why APEC remains such a crucial element of regional economic architecture and defines an agenda going forward to which regional leaders should aspire. Here is a first rate exposition of the priorities for regional cooperation in Asia and the Pacific. --Peter Drysdale, Professor Emeritus, Australian National University
Title from publisher's bibliographic system (viewed on 24 Nov 2015).
Keywords: Asia Pacific Economic Cooperation (Organization); Asian cooperation; Pacific Area cooperation; Asia -- Economic integration; Pacific Area -- Economic integration